Supersaturated Gel Formulation (SGF) of Atorvastatin at a Maximum Dose of 80 mg with Enhanced Solubility, Dissolution, and Physical Stability - Jin Woo Park; Sa-Won Lee; Jun Hak Lee; Sung Mo Park; Sung Jun Cho; Han-Joo Maeng; Kwan Hyung Cho (Gels)
The objective of this work was to develop a supersaturated gel formulation (SGF) loaded with the maximum atorvastatin calcium trihydrate (ATR) dose. The maximum dose strength of ATR needs to be reduced through improving solubility and dissolution rate to mitigate side effects due to the necessity of taking high doses. ATR has highly pH-dependent solubility at 37 °C, leading to poor solubility (<10 μg/mL) in stomach acid (pH 1.2). Among the various molecular weights of polyethylene glycols (PEGs) and surfactants, PEG 200 and d-α-tocopheryl polyethylene glycol 1000 succinate (TPGS) were selected as the solubilizer and precipitation inhibitor for ATR, respectively. PEG 200 demonstrated very high solubility for ATR (>60%, w/w), and the combined use of TPGS and PEG 200 formed an organogel state and suppressed ATR precipitation, showing 15-fold higher dispersion solubility in buffer solution at pH 1.2 compared to the formulation with PEG 200 alone. The optimal SGF composition (ATR/PEG 200/TPGS = 10/60/30, w/w) exhibited an over 95% dissolution rate within 2 h at pH 1.2, compared to less than 50% for the original commercial product. In a transmission electron microscope analysis, the SGF suppressed ATR precipitation and revealed smaller precipitated particles (<300 nm) compared to the control samples. In the XRD analysis, the SGF was physically stable for 100 days at room temperature without the recrystallization of ATR. In conclusion, the SGF suggested in this work would be an alternative formulation for the treatment of dyslipidemia with enhanced solubility, dissolution, and physical stability.